Adaptive set-point control system for microbial cultivation processes - Levišauskas, Donatas; Simutis, Rimvydas; Galvanauskas, Vytautas (Nonlinear Analysis: Modelling and Control, 2016)
A control system for set-point control of microbial cultivation process parameters is developed, in which a tendency model is applied for controller adaptation to process nonlinearity and time-varying operating conditions. The tendency model is updated on-line and introduced into control algorithm for prediction of steady-state control action and returning of feedback controller. The control system was tested for controlling dissolved oxygen concentration in batch operating mode bioreactor under extreme operating conditions. In simulation experiments, the control system demonstrates fast adaptation, robust behaviour and significant improvement in control performance compared to that of fixed gain controller.